2020
DOI: 10.1002/trc2.12073
|View full text |Cite
|
Sign up to set email alerts
|

Advancing combination therapy for Alzheimer's disease

Abstract: The study of Alzheimer's disease (AD) has led to an increased understanding of the multiple pathologies and pathways of the disease. As such, it has been proposed that AD and its various stages might be most effectively treated with a combination approach rather than a single therapy; however, combination approaches present many challenges that include limitations of non‐clinical models, complexity of clinical trial design, and unclear regulatory requirements. The Alzheimer's Association Research Roundtable me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Anti-tau agents already are in clinical trial, leading to consideration of combining anti-amyloid and anti-tau therapies [154]. Other potential combinations of therapies that have diverse mechanisms of action could include agents that address neuroinflammation, apolipoprotein E, mitochondrial modifiers, free radicals, autophagy, or the disrupted blood-brain barrier [44,155]. In addition, future studies should explore the potential role of human induced pluripotent stem cells (hiPSCs) in AD treatment, however to improve the interpretation of hiPSC experiments, more effective animal models and access to primary or age-matched cells from the human CNS are needed (Table 3).…”
Section: Combination Therapies In Prevention Trialsmentioning
confidence: 99%
“…Anti-tau agents already are in clinical trial, leading to consideration of combining anti-amyloid and anti-tau therapies [154]. Other potential combinations of therapies that have diverse mechanisms of action could include agents that address neuroinflammation, apolipoprotein E, mitochondrial modifiers, free radicals, autophagy, or the disrupted blood-brain barrier [44,155]. In addition, future studies should explore the potential role of human induced pluripotent stem cells (hiPSCs) in AD treatment, however to improve the interpretation of hiPSC experiments, more effective animal models and access to primary or age-matched cells from the human CNS are needed (Table 3).…”
Section: Combination Therapies In Prevention Trialsmentioning
confidence: 99%
“… 30 , 43 , 44 Thus, single‐target therapies effective in reducing risk of AD will not necessarily be effective for treatment for AD. 45 , 46 However, combination therapies tailored to the cascade of risk factors still hold potential. Because risk factor biology is linked to the pathophysiology of AD, combination therapy that targets the preclinical risk factor profile could provide a combinatorial strategy to treat AD.…”
Section: Discussionmentioning
confidence: 99%
“…24 Therefore, the identification of combinatorial drug targets emerges as an essential approach to develop an effective combinatorial strategy in combating neurodegenerative tauopathies. 25 This indicated that dmyc and gsk3β can be exploited as a combinatorial drug target to accomplish an efficient amelioration against tau toxicity. In our subsequent investigations, we established that dmyc and gsk3β functions in a linear pathway to curb tau etiology.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is worth mentioning that the complex nature of tauopathies, which is primarily due to the contribution of multiple cellular cascades affected by pathogenic tau molecules, a single genetic modifier or a molecule is unlikely to be efficient enough to drive a complete rescue. 10,[22][23][24][25] Therefore, the need of the hour is to identify more than one candidate gene(s), which can act synergistically to alleviate the toxic effects of human tau protein.…”
Section: Introductionmentioning
confidence: 99%